PERAN RESPONSIBLE MICA INITIATIVE (RMI) DALAM MENANGGULANGI FENOMENA PEKERJA ANAK DI TAMBANG MIKA DI INDIA PERIODE 2018-2019 - Nisrina Widyastuti (2022)
This study aims to discuss the role of the Responsible Mica Initiative (RMI) in the effort to protect the rights of children who are child labourers in mica mines in India, primarily in its first-years formed as an International Non-Governmental Organization (INGOs) which are also part of the Transnational Advocacy Network (TAN). The method used is qualitative that focuses on case studies of child labour in mica mines in India through secondary data obtained through literature reviews of annual reports of RMI, scientific articles, supporting books, and another supporting sources accessed from trusted scientific sites. The data that has been obtained through the literature review will be sorted and processed, then interpreted and presented in the form of this thesis. From the research process that has been done, this research shows that the role of RMI as an international non-state actor in the form of an INGO in addressing the issue of child labour in mica mines in India can be seen from its role as an INGO which is also part of a transnational advocacy network. RMI as an intelligent INGO is actively providing a responsible working environment in mica mines and community empowerment so that the children of mining workers-who are actually forced by circumstances to become mine workers-can continue to work while obtaining proper education and protection of their rights as mine workers. In addition, as an actor who is part of a transnational advocacy network, RMI plays a role in maintaining relationships with other global actors through various discussion forums up to the annual commemoration of the International Year Against Child Labour starting in 2021. Through this concept, it can be seen that RMI's role in addressing the issue of child labour in mica mines in India seems insignificant enough and is still mostly in the form of discussions and program plans in relations to the discussed programs' realization. This can be said as reasonable considering that in 2018-2019 RMI was only established so it still needs a lot of adjustments and stabilization. However, the existence of RMI has more or less helped to attract the attention and initiate actors and the public in general to take action in the matter of child labour in mica mines in India. Keywords: Responsible Mica Initiative (RMI), child labour, mica mines, international non-governmental organization, transnational advocacy network.